Comparison 2 methods of resistance training (conventional and bodypump) on the agility and vertical jump in male basketball players 16-18 years - Amir Baratı; Hamid Salımı; Nahid Adıbpour (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to compare an bodypump and resistance training on agility and vertical jump on male basketball players 16-18years. Therefore 36 teenage basketball players voluntarily chosen and randomly divided into three groups including: bodypump group (n=12,age 17 ± 0.5 year, height 179 ± 0.05 cm and a weight 69.26± 12.22 kg) and resistance group (n=12, age rangen 17± 0.6 years, range height 178 ± 0.09 cm and weight 68.55 ± 14.25 kg) and control group (n=12, age 17 ± 0.5 years, height 179 ± 0.06 cm, and the weight 70.06 ± 8 kg), respectively. Experimental groups were carried out of 8-weeks of typical training. Before and after 8 weeks, the subjects were tested. Vertical jump was measured by Sargent and agility was measured by T test. For analysis data one way ANCOVA and Bonferroni test were used. Measurements between groups indicated that the difference was significant, and Bonferroni test showed that between experimental and control groups difference was significant, but the difference between the experimental groups was not significant. It can be concluded, both methods had the same effect on vertical jump and agility. Therefore, in order for basketball players within 16-18 age group to improve them, they can utilize one of the two methods on their own choice. Coaches should be based on intensity, duration, discipline, control and supervise the performance, since bodypump method does not require expensive and complex devices, and can be performed with a number of dumbbell and barbell and control and supervise the performance due to the implementation of harmonic and simultaneous movements easier and the effectiveness of the conventional method was similar, for this reason can be suggested used in a large number of the club's athletes and the cost and time is important to them to be used.